2018
DOI: 10.1038/s41598-018-33391-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of polyketide synthase genes in the biocontrol fungus Clonostachys rosea

Abstract: Clonostachys rosea is a mycoparasitic fungus used for biological control of plant diseases. Its genome contains 31 genes putatively encoding for polyketide synthases (PKSs), 75% of which are arranged in biosynthetic gene clusters. Gene expression analysis during C. rosea interactions with the fungal plant pathogens Botrytis cinerea and Fusarium graminearum showed common and species-specific induction of PKS genes. Our data showed a culture media dependent correlation between PKS gene expression and degree of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 73 publications
1
90
1
3
Order By: Relevance
“…It is also possible that some of the highly up-regulated genes, particularly PKSs, are involved in fungal development and/or protection as well. For example, two up-regulated PKSs in C. rosea IK726 upon interaction with F. graminearum were previously identified; however deletion of one led to pigmentation loss, while deletion of the other reduced the antagonistic activity of C. rosea IK726 against F. graminearum (Fatema, 2017 ). Secondary metabolism-related secondary metabolites have also been associated with fungal sclerotial development (Calvo and Cary, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some of the highly up-regulated genes, particularly PKSs, are involved in fungal development and/or protection as well. For example, two up-regulated PKSs in C. rosea IK726 upon interaction with F. graminearum were previously identified; however deletion of one led to pigmentation loss, while deletion of the other reduced the antagonistic activity of C. rosea IK726 against F. graminearum (Fatema, 2017 ). Secondary metabolism-related secondary metabolites have also been associated with fungal sclerotial development (Calvo and Cary, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an excellent biological agent, C. rosea plays crucial roles in the biological control of many kinds of pathogens. To date, C. rosea has been reported to act against numerous fungal plant pathogens including Alternaria dauci, A. radicina, B. cinerea, B. aclada, Bipolaris sorokiniana, Drechslera teres, F. graminearum, F. verticillioides, F. The biological control mechanism of C. rosea against pathogens is primarily attributed to the secretion of CWDEs, and the production of secondary metabolites such as antibiotics and toxins, and the induction of plant resistance (Chatterton and Punja 2009;Fatema et al 2018). Although the constituents of fungal cell walls are complex, they are mainly composed of chitin, glucan and glycoproteins (Bowman and Free 2006).…”
Section: Role Of C Rosea In Biological Controlmentioning
confidence: 99%
“…Fatema et al (2018) demonstrated that two polyketide synthase genes, PKS22 and PKS29, play important roles in the synthesis of antifungal agents, clonorosein A-D that are effective against B. cinerea. Dubey et al (2016) found that the ABC transporter gene ABCG29 is involved in fungal adaptation to oxidative stress in the early stages of mycelial development and biocontrol of B. cinerea and Fusarium graminearum. Sun et al (2019a) indicated that the heat shock protein 70 gene, crhsp, had a remarkable effect on C. rosea morphological characteristics and significantly reduced its ability to parasitize S. sclerotiorum sclerotia.…”
Section: Introductionmentioning
confidence: 99%
“…This species has great potential for controlling various plant fungal diseases and promoting crop growth ( Atanasova et al, 2018 ), and functional genes in particular have attracted much attention. Fatema et al (2018) demonstrated that two polyketide synthase genes, PKS22 and PKS29 , play important roles in the synthesis of antifungal agents, clonorosein A–D that are effective against B. cinerea . Dubey et al (2016) found that the ABC transporter gene ABCG29 is involved in fungal adaptation to oxidative stress in the early stages of mycelial development and biocontrol of B. cinerea and Fusarium graminearum .…”
Section: Introductionmentioning
confidence: 99%